Alpine headwaters emerging from glaciers and rock glaciers host different bacterial communities: ecological implications for the future - Tolotti, M; Cerasino, L.; Donati, C.; Pindo, M.; Rogora, M.; Seppi, R.; Albanese, D. (Science of The Total Environment, 2020)
Mountain glacier shrinkage represents a major effect of the current global warming and 80–100% of the Alpine glaciers are predicted to vanish within the next few decades. As the thawing rate of mountain permafrost ice is much lower than for glacier ice, a shift fromglacial to periglacial dynamics is predicted for Alpine landscapes during the 21st century. Despite the growing literature on the impacts of deglaciation on Alpine hydrology and ecosystems, chemical and biological features ofwatersemerging fromAlpine rock glaciers (i.e. permafrost landforms composed by a mixture of ice and debris) have been poorly investigated so far, and knowledge on microbial biodiversity of headwaters is still sparse. A set of glacier-, rock glacier- and groundwater/precipitation-fed streams was investigated in the Italian Central Alps in late summer 2016, aiming at exploring bacterial community composition and diversity in epilithic and surface sediment biofilm and at verifying the hypothesis that rock glacierfed headwaters represent peculiar ecosystems fromboth a chemical and biological point of view. Rock glacier-fed waters showed high values of electrical conductivity and trace elements related to their bedrock lithology, and their highly diverse bacterial assemblages significantly differed from those detected in glacier-fed streams. Bacterial taxonomic composition appeared to be mainly related to water and substrate type, as well as to water chemistry, the latter including concentrations of nutrients and trace metals. The results of this study confirm the chemical and biological peculiarity of rock glacier-fed waters compared to glacial waters, and suggest a potential driving role of thawing permafrost in modulating future ecological traits of Alpine headwaters within the context of progressing deglaciation.